2013
DOI: 10.1177/0011128712470348
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Context and Police Vigor

Abstract: This study provides a partial test of Klinger’s ecological theory of police behavior using hierarchical linear modeling on 1,677 suspects who had encounters with police within 24 beats. The current study used data from four sources originally collected by the Project on Policing Neighborhoods (POPN), including systematic social observation, in-person interviews with officers, census data, and police crime records. It investigates the effects of neighborhood violent crime rates and concentrated disadvantage on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…Policing is a territorially organized enterprise, with agency demarcation determined by political boundaries, patrol and other sectors of large agencies demarcated by district boundaries within which police work groups operate, and work responsibilities within districts delimited by the beats that officers routinely patrol (Klinger, ). Within beats, officers’ territorial knowledge involves understanding of the threat contours of specific neighborhoods (Klinger, ; Sobol, Wu, and Sun, ), including “hot spots” with particularly high levels of crime (Weisburd, Groff, and Yang, ). Because policing is spatially organized, and because officers’ work orientations include such high doses of spatial awareness, future research should build on the current study by investigating how officers adapt their behavior to the threat environments in which they exercise their coercive power, including the ultimate power to take life.…”
Section: Discussionmentioning
confidence: 99%
“…Policing is a territorially organized enterprise, with agency demarcation determined by political boundaries, patrol and other sectors of large agencies demarcated by district boundaries within which police work groups operate, and work responsibilities within districts delimited by the beats that officers routinely patrol (Klinger, ). Within beats, officers’ territorial knowledge involves understanding of the threat contours of specific neighborhoods (Klinger, ; Sobol, Wu, and Sun, ), including “hot spots” with particularly high levels of crime (Weisburd, Groff, and Yang, ). Because policing is spatially organized, and because officers’ work orientations include such high doses of spatial awareness, future research should build on the current study by investigating how officers adapt their behavior to the threat environments in which they exercise their coercive power, including the ultimate power to take life.…”
Section: Discussionmentioning
confidence: 99%
“…Also, these places tend to be the areas where most police use‐of‐force incidents occur and also where most police misconduct cases arise (see Fagan and Davies ). These high‐crime, economically disadvantaged neighborhoods also tend to be subject to more control or coercive activities (Smith and Klein ), increased police vigor in handling suspects (Sobol, Wu, and Sun ), and in some cases, slower response time for service calls from police (Cihan ; though see Lee, Lee, and Hoover ). Additionally, stop‐and‐frisk methods, which are common in economically distressed areas of a city (Gelman, Fagan, and Kiss ), disproportionately target African Americans and Latinos at rates much higher than whites (Gelman et al.…”
Section: Policing and Surveillance In Neighborhoodsmentioning
confidence: 99%
“…White [21] found that certain categories of incidents, such as robberies and disturbance incidents, were more likely to result in police use of deadly force. However, studies examining the relationship between citizen characteristics (such as race, gender, and age) and police behavior (such as likelihood of arrests and citations, and use of force) have found mixed results [17]. Research on citizen characteristics has, moreover, been limited due to lack of publicly available data.…”
Section: Databasementioning
confidence: 99%
“…Finally, neighborhood features have also been studied as a potential predictor of police misconduct. Sobol [17] found that incidents in high-crime neighborhoods have a greater likelihood of ending in interrogation, search and/or arrest. Similarly, Terrill and Reisig [18] found that police officers were more likely to use higher levels of force in disadvantaged and high-crime neighborhoods.…”
Section: Databasementioning
confidence: 99%